Pre-tensioned fiber reinforced boards as potential alternative for light construction - Cerillo, Fayanna P. (2017)
This researched introduced a new and innovative building material using banana fibers that is industrially applicable for mass production, readily available in the Philippine local market and with characteristics that make it suitable as an alternative for light construction. Experimental methods included using 20kg concrete weights as pre-tensioning system on 3mm dia banana fiber ropes. The optimal spacing of the banana fiber ropes were tested using a manual three-point flexural test. The spacing tested were 18mm, 36mm, 54mm and 72mm and a control group without the banana fiber ropes on a 1200mmx600mmx20mm cement board. For the production of the material, aside from banana fibers, rice hull ash and cement are used instead of the common cement and sand mix of concrete. In conclusion, banana fibers when used as pre-tensioning reinforcement increase the material?s mechanical properties. The closer the distance between the fiber ropes, the greater its mechanical properties as the 18mm spacing exhibited the highest flexural strength and load bearing capacity compared to the rest of the spacing and with the control group. It is also a light weight material due to the rice hull ash. This pilot study on pre-tensioning systems using natural fibers requires further studies for improvement such as using different varieties of bananaand other kinds of natural fiber.